EFFECT OF THE ADDITION PAPAIN IN COMMERCIAL FEED WITH DIFFERENT DOSAGE ON THE GROWTH OF FISH NILEM SEEDS (Osteochilus hasselti) IN RECIRCULATION SYSTEM - Witri Yulia Sari; Mulyadi Mulyadi; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe aim of the study was to determine the best time administration of papain doses best on commercial clothes to increase the growth of nilem fish seeds (Osteochilus hasselti).in recirculation systems. Culture vessel in the form of aquarium of 60 x 40 x 40 centimeters of 15 aquarium with stocking density of 11 fish/m3. This research was using experimental method by completely random design (RAL) one factor with five treatments and three replicationsThe treatment applied was the feeding of the enzyme containing papain with different dosages: P0= without the addition of the papain enzyme, P1=the addition of the enzyme papain 1,25%/kg of feed, P2=the addition of the enzyme papain 2,25%/kg of feed, P3= the addition of the enzyme papain 3,25%/kg of feed and P4= the addition of the enzyme papain 4,25%/kg of feed. The results showed that the addition of rElGH in feed, showed highly significant effect (P<0.05) on the total weight, total length, specific growth rate, feed conversion ratio, and no significant effect (p>0.05) to survival rate. The best growth rates was found in treatment P1 with total weight: 5.75±0.02gram, total length: 4.06±0.05 cm, specific growth rate: 4.32±0.02% per day, feed conversion  ratio: 1.23±0.01and survival rate: 100±0.00%.Keywords:Nilem fish, Papain Enzyme